Perancangan Aplikasi Penjualan Pipa pada PT. Sumber Anugrah Berkah Abadi - Iqbal Fahrozi; Nandar Rustandar; Bagas Gemilang Ryadi; Thoyyibah. T (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Pipe Sales Application Design at PT. Sumber Anugrah Berkah Abadi is a design that is helpful in providing and presenting information about company profiles and products to be marketed. Information technology can assist companies in solving problems and determining what business strategy to use. One form of trading business strategy on the internet is e-commerce, by utilizing e-commerce it will make it easier for prospective buyers to view product information, and make transactions easily. In addition, sellers can also expand the area of marketing their products. This application is expected to support and be useful in presenting the information needed by prospective buyers. The design of this application uses data collection methods, interviews with field supervisors, observations, the waterfall method with the Software Development Life Cycle (SDLC) approach to build this application using Visual Studio Code 1.73.1, HTML, CSS, PHP, JavaScript and MySQL as the database. With this web-based application, it can help increase sales and present the information needed by potential buyers, and prospective buyers only use electronic devices to run this application to find out information and order the desired product remotely.